PEMBUATAN TAMAN BELAJAR KI HAJAR DEWANTARA (PTBK) DI DUKUH KARANG PASEBAN BAYAT - Yuniantoro, Nanag; Isnanto, Dwi; Fitriadewi, Ardiyanti; Winjani, Andina (Pelita - Jurnal Penelitian Mahasiswa UNY, 2015)
Abstract At Karang, Paseban, Bayat from 2008 to 2013 there were 1 to 2 elementary school children who did not pass to the next grade of their elementary education. One of the reasons is their low reading interest. They would rather play games than read. The long term goal of this program is to improve the quality of education and learning community to develop creativity, whereas the short term one is to create a kind of learning park named Ki Hajar Dewantara and organize activities that are beneficial to the society. The method of the program consists of preparing the permit, equipment and materials, and socializing the program to the community, and implementing, monitoring, evaluating, and completing the program. The results of the program are a learning park named Ki Hajar Dewantara at Karang, Paseban, Bayat, establishing a board comprising of the young people at Karang to take care of the park, and a change in the mindset of the children and youth in spending the leisure time, which is proved by the increasing number of visits to the park during the six-week study, from 12 children at the end of June to 59 children per week in the beginning of August. The existence of the park brings the benefit of the culture of reading in the society.